Ten-year long-term outcomes of conventional and eversion carotid endarterectomy. Multicenter study - Yu. V. Belov; A. N. Kazantsev; R. A. Vinogradov; A. V. Korotkikh; V. V. Matusevich; S. V. Artyukhov; E. Yu. Kachesov; D. V. Shmatov; A. B. Zakeryaev; P. V. Sukhoruchkin; A. A. Erofeev; A. R. Shabaev; et al. (Российский кардиологический журнал, 2022)
Aim. To analyze the immediate and long-term outcomes of eversion and conventional carotid endarterectomy (CE) with patch angioplasty.Material and methods. For the period from February 1, 2006 to September 1, 2021, the present retrospective multicenter open comparative study included 25106 patients who underwent CE. Depending on the technique of operation, the following groups were formed: group 1 (n=18362) — eversion CE; group 2 (n=6744) — conventional CE with patch angioplasty. The long-term follow-up period was 124,7±53,8 months.Results. In the hospital postoperative period, the groups were comparable in incidence of all complications: lethal outcome (group 1: 0,19%, n=36; group 2: 0,17%, n=12; p=0,89; odds ratio (OR) =1,1; 95% confidence interval (CI) =0,57- 2,11); myocardial infarction (MI) (group 1: 0,15%, n=28; group 2: 0,13%, n=9; p=0,87; OR=1,14; 95% CI=0,53-2,42); stroke (group 1: 0,33%, n=62; group 2: 0,4%, n=27; p=0,53; OR=0,84; 95% CI=0,53-1,32); bleeding with hematoma formation (group 1: 0,39%, n=73; group 2: 0,41%, n=28; p=0,93; OR=0,95; 95% CI=0,61-1,48); internal carotid artery (ICA) thrombosis (group 1: 0,05%, n=11; group 2: 0,07%, n=5, p=0,9; OR=0,8; 95% CI=0,28-2,32). In the long-term follow-up, the groups were comparable only in MI incidence: group 1: 0,56%, n=103; group 2: 0,66%, n=45; p=0,37; OR=0,84; 95% CI=0,59-1,19. All other complications were more frequent after conventional CE with patch angioplasty: all-cause death (group 1: 2,7%, n=492; group 2: 9,1%, n=616; p<0,0001; OR=0,27; 95% CI=0,24-0,3); lethal ischemic stroke (group 1: 1,0%, n=180; group 2: 5,5%, n=371; p<0,0001; OR=0,17; 95% CI=0,14-0,21); non-lethal ischemic stroke (group 1: 0,62%, n=114; group 2: 7,0%, n=472; p<0,0001; OR=0,08; 95% CI=0,06-0,1); ICA restenosis >60%, requiring re-revascularization (group 1: 1,6%, n=296; group 2: 12,6%, n=851; p<0,0001; OR=0,11; 95% CI=0,09-0,12). Thus, the composite endpoint (lethal ischemic stroke + non-lethal ischemic stroke + MI) after conventional CE with patch angioplasty was more than 6 times higher than this parameter of eversion CE: group 1: 2,2%, n=397; group 2: 13,2%, n=888; p<0,0001; OR=0,14; 95% CI=0,12-1,16.Conclusion. Conventional CE with patch angioplasty is not prefer for cerebral revascularization in the presence of hemodynamically significant ICA stenosis due to the high prevalence of deaths, stroke, and ICA restenosis in the long-term follow-up.